PENGARUH PEMBIAYAAN MURABAHAH TERHADAP RETURN ON ASSET (ROA) PADA PT. BANK ACEH SYARIAH - Fariza, Cut; Ayumiati, Ayumiati; Muksal, Muksal (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2023)
This study aims to determine the Effect of Murabahah Financing on the Profitability of PT. Bank Aceh Syariah (2019-2021 Period) and this research is secondary data based on the results of the monthly financial reports of PT. Bank Aceh Syariah for the 2019-2021 period. This type of research is quantitative research with a simple linear regression analysis method. The results of the t test show that tcount > ttable (2.909> 1.68) and a significance of 0.014 is less than 0.05, meaning that murabaha income has a positive and significant effect on profitability (ROA).